International Consensus Conference for Advanced Breast Cancer, Lisbon 2019: ABC5 Consensus - Assessment by a German Group of Experts - Thomssen, Christoph; Lüftner, Diana; Untch, Michael; Haidinger, Renate; Würstlein, Rachel; Harbeck, Nadia; Augustin, Doris; Briest, Susanne; Ettl, Johannes; Fasching, Peter; Förster, Frank; Kurbacher, Christian M.; et al. (Breast Care, 2020)
The 5th International Consensus Conference for Advanced Breast Cancer (ABC5) took place on November 14-16, 2019, in Lisbon, Portugal. Its aim is to standardize the treatment of advanced breast cancer based on the available evidence and to ensure that all breast cancer patients worldwide receive adequate treatment and access to new therapies. This year, the conference focused on developments and study results in the treatment of patients with hormone receptor-positive/HER2-negative breast cancer as well as precision medicine. As in previous years, patient advocates from around the world were integrated into the ABC conference and had seats on the ABC consensus panel. In the present paper, a working group of German breast cancer experts comments on the results of the on-site ABC5 consensus votes by ABC panelists regarding their applicability for routine treatment in Germany. These comments take the recommendations of the Breast Committee of the Gynecological Oncology Working Group (Arbeitsgemeinschaft Gynäkologische Onkologie; AGO) into account. The report and assessment presented here pertain to the preliminary results of the ABC5 consensus. The final version of the statements will be published in Annals of Oncology and The Breast.
CRIS-Team Scopus Importer:2020-02-25